Making the best of it: nitroxide-mediated polymerization of methacrylates via the copolymerization approach with functional styrenics. Issue 2 (29th November 2019) - Schmidt, Aaron C.; Turgut, Hatice; Le, Dao; Beloqui, Ana; Delaittre, Guillaume
Abstract : The addition of 5 mol% of functional styrenics imparts control to the SG1-mediated polymerization of methacrylates and provides access to nanostructured functional methacrylic materials. Abstract : The SG1-mediated solution polymerization of methyl methacrylate (MMA) and oligo(ethylene glycol) methacrylate (OEGMA, M n = 300 g mol −1 ) in the presence of a small amount of functional/reactive styrenic comonomer is investigated. Moieties such as pentafluorophenyl ester, triphenylphosphine, azide, pentafluorophenyl, halide, and pyridine are considered. A comonomer fraction as low as 5 mol% typically results in a controlled/living behavior, at least up to 50% conversion. Chain extensions with styrene for both systems were successfully performed. Variation of physical properties such as refractive index (for MMA) and phase transition temperature (for OEGMA) were evaluated by comparing to 100% pure homopolymers. The introduction of an activated ester styrene derivative in the polymerization of OEGMA allows for the synthesis of reactive and hydrophilic polymer brushes with defined thickness. Finally, using the example of pentafluorostyrene as controlling comonomer, it is demonstrated that functional PMMA- b -PS are able to maintain a phase separation ability, as evidenced by the formation of nanostructured thin films.